The Representation of Women in Various Genres of Japanese Comics: a Semiotic Study - Jayaputri, Herlandri Eka (Yayasan Nurul Iman Muara Gading Mas, 2024)
Manga, or Japanese comics, have garnered immense popularity in Indonesia, appealing to readers of all ages with their diverse fictional narratives. Across genres like action, romance, comedy, and supernatural, manga portrays a myriad of characters and scenarios, from lone male protagonists to shy girls exploring romantic dynamics. Yet, amidst its widespread appeal, manga often depicts female characters as mere sexual objects, sparking scholarly inquiry into their representation. Through Roland Barthes’ semiotic lens, researchers dissect the portrayal of women in various manga genres, uncovering prevalent ideologies. While women exude body confidence, they are frequently subjected to sexual exploitation by male characters, ranging from intimate gestures to harassment. This pervasive depiction reinforces the objectification of women, normalizing harmful behaviors within manga narratives, prompting critical examination of gender dynamics in popular culture.